Multiple criteria decision-making techniques in transportation systems: a systematic review of the state of the art literature - Mardani, Abbas; Zavadskas, Edmundas K.; Khalifah, Zainab; Jusoh, Ahmad; Md Nor, Khalil (Transport, 2016)
The main goal of this review paper is to provide a systematic review of Multiple Criteria Decision-Making (MCDM) techniques in regard to transportation systems problems. This study reviewed a total of 89 papers, published from 1993 to 2015, from 39 high-ranking journals; most of which were related to transportation science and were extracted from the Web of Science and Scopus databases. Papers were classified into 10 main application areas and nine transport infrastructure. Furthermore, papers were categorized based on the author(s) and year, name of the journal in which they were published, technique and approach, author(s) nationality, application area and scope, study purpose, gap and research problem and results and outcome. The results of this study indicated that more papers on MCDM in 2013 than in any other year. AHP and Fuzzy-AHP methods in the individual methods and hybrid MCDM and fuzzy MCDM in the integrated methods were ranked as the first and second methods in use, respectively. The Transportation Research Part A: Policy and Practice was the most significant journal in this study, with 13 publications on the topic. Finally, service quality was ranked as the first application area and airline industry was ranked as the first transport infrastructure that applied MCDM techniques. First published online: 18 Dec 2015